GMO1 - WHAT IS IT AND WHY DO WE NEED IT!? (Annual of the Faculty of Philosophy in Skopje, 2024)
Bioethical thinking regarding biotechnology should play an important rolein our lives, views and legislation. The main debates have been and still are over theregulation, safety and moral status of certain applications of modern biotechnology,such as GMOs. There are fears about the technology being autonomous without publiccontrol due to its strategic nature. Awareness of technological impact on modern life isbecoming more apparent as the application of biotechnology continues to develop. Howthen can we create a platform for handling biotechnology in a way that aligns with ourviews on the good life, ie. in a healthy, beneficial and environmentally sustainable way?This article therefore raises for discussion some important issues to considerregarding the ethical dimensions of technology and how it is used. Is it applied to thegreater good? And do current regulations, or the lack of them, violate our responsibilitiesto others by not allowing them to choose whether they knowingly and voluntarilyassume the risks of ingesting these GM substances?
Keywords: GMO; bioethics; biotechnology; nature; responsibility